Cinética e mecanismo da reação de reforma de etanol com vapor d'água sobre catalisador bimetálico Cu-Ni/NbxOy - Silva, Fernandes Alves da (2017)
The use of fuel cells has been pointed out as one of the best technologies for energy generation since they present high efficiency and low emission of harmful gases to the environment, like NOx and CO, principally when these devices work with hydrogen. This fuel can be acquired from many sources, as ethanol steam reforming, which generates energy withouth using no-renewable sources. In addition, the use of this bioalcohol as a source of hydrogen has a closed carbon cycle, not contributing to CO2 emissions increase, one of those responsible for the greenhouse effect. The choice of the catalyst, as well as reaction conditions, directly affects the process of ethanol-to-hydrogen conversion. Therefore, kinetics of the ethanol steam reforming reaction on the Cu-Ni/NbxOy catalyst was investigated since 400 ºC to 500 °C range. This catalyst shows a good selective and yield for production of H2 and CO2, besides low formation of CH4, no CO and dehydration products. The catalyst was synthesized by coprecipitation method which presented different niobium pentoxide structures and mixed oxide between niobium pentoxide and copper oxide, detected through the XRD and TPR-H2 analyses. It was observed that the metal-support interaction was favored. TGA/DSC profiles demonstrated high thermal stability, while selective chemisorption and SEM images indicated high dispersion of the active phase. The catalytic tests as a function of the contact time demonstrated that the steps that comprise the global process are dehydrogenation to acetaldehyde, decomposition to methane and carbon monoxide and water-gas shift reaction for production of CO2, which allowed proposing a mechanism for the ethanol reforming reaction. The kinetic data obtained in differential conditions, withouth diffusional effects, led to different rate expressions considering several determining steps, and the experimental data were satisfactorily fitted. The dehydrogenation and decomposition models presented the best correlation, while the CH intermediary decomposition model was not so good. The Power Law equation also presented low deviations between predicted and observed data, but it is restricted to the range of composition in which it was fitted. By-products and products were added to the feed flow system and the experimental reaction rates were compared to the models, which allowed the validation of the expressions. It was estimated the global activation energy, 373 kJ/mol. The kinetic models were suitable to represent the ethanol steam reforming for hydrogen production in the reaction system used.